Optimization of stocking density for successful larval rearing of Labeo dyocheilus in coldwater condition - Gupta, Monika; Pandey, N. N.; Tiwari, V. K.; Singh, Raghabendra; Prakash, Chandra; Chaturvedi, C. S. (Journal of the Inland Fisheries Society of India, 2019)
An attempt was taken to find out the optimum stocking density of the Labeo dyocheilus larvae for better recovery of fry in terms of survival and growth at different stocking densities i.e. 1, 2, 3, 4 larvae L-1 each with three replicates. Larvae were stocked in plastic tubs having average length of 4.3 Â± 0.10 mm and weight of 0.007 Â± 0.01 g. Growth performance of fish larvae was significantly affected by the stocking density and found maximum with lower socking density and minimum with higher stocking density. Optimumstocking density of L. dyocheilus for larval rearing was found 2 larvae L-1. It may be advantageous to maintain healthy seed for the successful larval rearing for the mass seed production that could be used for wild stock augmentation in the natural resources and for aquaculture of this species in hills.Keywords Stocking density, polylined tank, larval rearing, stock augmentation